Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/cell.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Cloned Bovine Embryos Produced from Oocytes Enucleated by Fluorescence Metaphase II Imaging Using a Conventional Halogen-Lamp Microscope

Abstract: Enucleation of a recipient oocyte is one of the key processes in the procedure of somatic cell nuclear transfer (SCNT). However, especially in bovine species, lipid droplets spreading in the ooplasm hamper identification and enucleation of metaphase II (MII) chromosomes, and thereby the success rate of the cloning remains low. In this study we used a new experimental system that enables fluorescent observation of chromosomes in living oocytes without any damage. We succeeded in visualizing and removing the MII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In cattle, although the blastocyst production is similar to that obtained in in vitro production of embryos (IVEP), (Iwamoto et al, 2015;Song et al, 2015;Jeong et al, 2013;Kato et al, 2000), a high rate of fetal loss is observed at the beginning of pregnancy (Keefer, 2015). These losses generally occur during placentation and have been related to epigenetic changes caused by failures in reprogramming of the differentiated donor cells (Campbell et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In cattle, although the blastocyst production is similar to that obtained in in vitro production of embryos (IVEP), (Iwamoto et al, 2015;Song et al, 2015;Jeong et al, 2013;Kato et al, 2000), a high rate of fetal loss is observed at the beginning of pregnancy (Keefer, 2015). These losses generally occur during placentation and have been related to epigenetic changes caused by failures in reprogramming of the differentiated donor cells (Campbell et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Hence, a more recent method introduces fluorescence-labelled antibodies, which can be injected into the oocytes. These antibodies will bind to chromosomes and are visible under a halogen-lamp microscope [12].…”
Section: Removal Of Zona Pellucida and Enucleationmentioning
confidence: 99%
“…Moreover, lipid droplets in the ooplasm obstruct identification and enucleation of metaphase II (MII) chromosomes, especially in bovine species, ultimately affecting the efficiency of the process. To overcome this problem, a new experimental system have been employed, which is based on fluorescent observation of chromosomes in living oocytes without any damage by injecting fluorescence-labeled antibody conjugates that bind to chromosomes and fluorescent observation using a conventional halogen-lamp microscope [ 34 ].…”
Section: Step By Step Guide To Hmcmentioning
confidence: 99%